The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1523/jneurosci.2049-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Blocking Memory Reconsolidation Reverses Memory-Associated Changes in Glutamate Receptor Expression

Abstract: It has been reported that consolidated memories can return to a labile state when reactivated and undergo a process of re-storage, termed reconsolidation, required for later recall. We investigated memory for a nonassociative learning task (habituation) and found that memory for this task also undergoes reconsolidation after recall. To investigate reconsolidation, we first demonstrated that adult Caenorhabditis elegans are capable of reliable memory 48 h after habituation training ( p Ͻ 0.05). When heat shock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
62
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 35 publications
9
62
0
Order By: Relevance
“…As would be expected for long-term memory, blocking protein synthesis during training (with heat shock) blocked consolidation of the memory (Beck and Rankin 1995). Long-term habituation was also sensitive to reconsolidation blockade-habituated worms given reminder taps followed by heat shock lost the memory of habituation training (Rose and Rankin 2006). These data suggest that long-term mechanosensory habituation shares features of long-term memory described in other organisms.…”
Section: Long-term Memorysupporting
confidence: 59%
“…As would be expected for long-term memory, blocking protein synthesis during training (with heat shock) blocked consolidation of the memory (Beck and Rankin 1995). Long-term habituation was also sensitive to reconsolidation blockade-habituated worms given reminder taps followed by heat shock lost the memory of habituation training (Rose and Rankin 2006). These data suggest that long-term mechanosensory habituation shares features of long-term memory described in other organisms.…”
Section: Long-term Memorysupporting
confidence: 59%
“…In these amnesic animals, this also leads to the absence of ERK and its downstream transcription factors in the nucleus accumbens (see also Valjent et al 2006, who show a reduction in ERK and GluA1 phosphorylation using a similar procedure). Studying mechanisms of long-term habituation in Caenorhabditis elegans, Rose and Rankin (2006) showed that administering heat-shock or the non-N-methyl-D-aspartate (NMDA) glutamatergic antagonist, DMQX, after reactivation of a consolidated memory dramatically returns expression of aamino-3-hydroxy-5-methyl-4-isoxazolepropionic (AMPA) receptors in the mechanosensory neuron to a level typical for naïve animals (Rose and Rankin 2006). Importantly, the reconsolidation effects in all of these studies were contingent on memory reactivation-in the absence of a reminder the amnesic treatments were ineffective.…”
Section: Reconsolidation and The Dynamic Nature Of Memorymentioning
confidence: 99%
“…Pharmacological blockade of non-NMDA (N-methyl-D-aspartic acid) type glutamate receptors with 6, 7-dinitroquinoxaline-2,3-dione (DNQX) during reminder also eliminated the 48-h retention. Furthermore, the expression level of specific glutamate receptor subunit (GLR-1) decreased significantly in trained animals compared with untrained controls, and the effect of training on GLR-1 levels was reversed if the trained animals were given a reminder immediately followed by heat shock [24] . Therefore, both the behavioral expression of long-term memory for habituation and a cellular correlation of that memory can be altered after retrieval in C. elegans [24] .…”
Section: Intermediate Memory For Habituationmentioning
confidence: 99%
“…Therefore, both the behavioral expression of long-term memory for habituation and a cellular correlation of that memory can be altered after retrieval in C. elegans [24] . In addition, similar mechanisms are involved in the control of memory consolidation and memory reconsolidation, since conditions that impair memory consolidation similarly disrupt memory reconsolidation [24] . These findings also confirm the previous observation that GLR-1 cluster density was closely correlated with the expression of memory for habituation.…”
Section: Intermediate Memory For Habituationmentioning
confidence: 99%
See 1 more Smart Citation